2020
DOI: 10.3390/ijerph17165659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birdsong Soundscape on Perceived Restorativeness in an Urban Park

Abstract: Natural soundscapes have beneficial effects on the perceived restorativeness of an environment. This study examines the effect of birdsong, a common natural soundscape, on perceived restorativeness in Harbin Sun Island Park in China. Eight sites were selected and a series of questionnaire surveys on perceived restorativeness soundscape scale (PRSS) of four birdsong types were conducted during summer and winter. Two-hundred and forty respondents participated in this survey. Analysis of the survey results shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Although a large number of studies have shown that natural sounds have a better restorative effect than human-based sounds, there is a lack of studies comparing different kinds of natural sounds or composite sound sources. For example, Wei Zhao et al only reported the effects of birdsong on the restorative nature of urban parks [27], and Annerstedt et al only demonstrated better stress relieving effects of birdsong and water flow sound exposure than no sound exposure [19]. While there are many studies on the subject of park soundscapes globally, there are still very few studies from Asia, especially those that take a multidimensional approach to the study of soundscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of studies have shown that natural sounds have a better restorative effect than human-based sounds, there is a lack of studies comparing different kinds of natural sounds or composite sound sources. For example, Wei Zhao et al only reported the effects of birdsong on the restorative nature of urban parks [27], and Annerstedt et al only demonstrated better stress relieving effects of birdsong and water flow sound exposure than no sound exposure [19]. While there are many studies on the subject of park soundscapes globally, there are still very few studies from Asia, especially those that take a multidimensional approach to the study of soundscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Ratcliffe et al (2013Ratcliffe et al ( , 2016Ratcliffe et al ( , 2020 shows that there is variation even within a single category of nature sound (bird songs and calls): songbirds are qualitatively and quantitatively regarded as more pleasant, relaxing, and potentially restorative than birds which make rough, noisy, and simple calls, or those which have negative meanings or associations. Zhao et al (2020) have linked crow sounds specifically to lower evaluations of the perceived restorativeness of park soundscapes, while woodpeckers and sparrows are related to more positive evaluations. These findings suggest that variations in preference and perceived restorative value exist even between types of nature sound within the same category.…”
Section: Not All Sounds In Nature Are Perceived As Pleasantmentioning
confidence: 99%
“…In the third and fourth sections, the three types that constitute a soundscape as defined by Kraus [40] (abiotic natural sounds from the physical environment, nonhuman biological sounds emitted by all organisms in a given habitat, and anthropomorphic sounds emitted by stationary and moving man-made objects) were used as the basis for classifying the types of soundscapes in the questionnaire. On this basis, the scales used in the study of landscape perception by scholars such as Zheng Zhao [41] and the scales involved in the study of urban forest park soundscape by Wei Zhao [42] and Banu Chitra [43], respectively, were used, and the scales used in this study were appropriately adjusted and modified by combining the ISO [44] definition and classification of soundscape and the actual situation of Beigushan Forest Park in Lianyungang. The third part focused on the understanding of individual visual landscape preferences, mainly using a five-point Likert scale (strongly dislike (−2), dislike (−1), average (0), like (1), and like very much (2)) to illustrate their overall preferences for visual landscapes.…”
Section: Questionnaire Designmentioning
confidence: 99%